Pelaksanaan Ganti Rugi dalam Pelepasan Hak Atas Tanah untuk Pelebaran Jalan - Arion Tampubolon; I Made Minggu Widyantara; Kade Richa Mulyawati (Warmadewa Press, 2022)
Land is a very important value for people's lives, so it can be used as a goal of prosperity for the life of the nation. Land used for public purposes is one of the problems often faced by Indonesia, including Sidikalang City, Dairi Regency, North Sumatra Province regarding compensation for community land used for agriculture and road repairs. This study aims to reveal the legal process and steps taken regarding land compensation for the development of Sidikalang city. This study uses empirical legal research with legal and conceptual approaches and data collection techniques used are observation, interviews and library research. The data sources in this research are primary and secondary data. The results of the study reveal the procedure for compensation for road widening development as regulated in Presidential Regulation 148/2015 which amends the fourth amendment to Presidential Regulation 71/2012 concerning the Realization of Land Purchases for Development of Social Uses as well as a path or profession that is likely to be determined, namely controversial and non-controversial. . In this case, the land conflict resolution process is mediation or negotiation to reach an agreement between the parties.